3-Methyl-1-butanol production in Escherichia coli: random mutagenesis and two-phase fermentation - Connor, Michael R. (Springer-Verlag, 2010)
Interest in producing biofuels from renewable sources has escalated due to energy and environmental concerns. Recently, the production of higher chain alcohols from 2-keto acid pathways has shown significant progress. In this paper, we demonstrate a mutagenesis approach in developing a strain of Escherichia coli for the production of 3-methyl-1-butanol by leveraging selective pressure toward l-leucine biosynthesis and screening for increased alcohol production. Random mutagenesis and selection with 4-aza-d,l-leucine, a structural analogue to l-leucine, resulted in the development of a new strain of E. coli able to produce 4.4 g/L of 3-methyl-1-butanol. Investigation of the host’s sensitivity to 3-methyl-1-butanol directed development of a two-phase fermentation process in which titers reached 9.5 g/L of 3-methyl-1-butanol with a yield of 0.11 g/g glucose after 60 h.